2015
DOI: 10.1111/cmi.12547
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances: role of mycolactone in the pathogenesis and monitoring ofMycobacterium ulceransinfection/Buruli ulcer disease

Abstract: SummaryInfection of subcutaneous tissue with Mycobacterium ulcerans can lead to chronic skin ulceration known as Buruli ulcer. The pathogenesis of this neglected tropical disease is dependent on a lipid‐like toxin, mycolactone, which diffuses through tissue away from the infecting organisms. Since its identification in 1999, this molecule has been intensely studied to elucidate its cytotoxic and immunosuppressive properties. Two recent major advances identifying the underlying molecular targets for mycolactone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 60 publications
2
100
0
Order By: Relevance
“…On the other hand, other researchers reported that mycolactone inhibited the function of the Sec61 translocon [7,9,26]. Sec61 mediates antigen transport across endosomal membranes and affects cross-presentation in dendritic cells [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, other researchers reported that mycolactone inhibited the function of the Sec61 translocon [7,9,26]. Sec61 mediates antigen transport across endosomal membranes and affects cross-presentation in dendritic cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…WiskottAldrich syndrome protein (WASP) and neural WASP (N-WASP) were reported as direct binding targets of mycolactone [7,21]. These proteins are members of a family of scaffold proteins transducing signals involved in the dynamic remodeling of the actin cytoskeleton [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The central role of mycolactone in the pathogenesis and its potential application as a biomarker for BU has been reviewed by our group. 49 …”
Section: Diagnostic Confirmationmentioning
confidence: 99%